Laundry Q: Korelasi Antara Ancaman Klausula Baku dan Kritik Terhadap Undang-Undang Perlindungan Konsumen - Rahmat Rahmat (Khatulistiwa, 2016)
Standard clauses are an accumulation of business and non-business factors, and follow a uniform pattern. The principles of consumer protection contract, either introduced by Law No. 8 /1999 or by experts, have yet to contain standard contracts and clauses. As a result, even though Laundry Q combined three principles of the contract, the composition of standard clauses consist of exonerated and prohibited clauses. Besides containing the internal weakness, this law has weak supervision not to mention law enforcement. Standard clauses only covers a small part of clauses on the formulation of business actors. The executive and legislative body should act. Certified standard clauses, the revision of Article 18 of Law No. 8 /1999, and judicial review of this article by the Constitutional Court needs to be done.